HUBUNGAN E-BUSINESS DAN SCM DALAM MANAJEMEN INTERNAL PT TSABITA CAKE & BAKERY - Azifa Habiba (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
This study aims to analyze the relationship between e-business and SCM in the internal management of PT Tsabita Cake & Bakery because the company, which initially still used a manual system, eventually switched to using SCM and e-business. The method used is a quantitative approach and correlation analysis to analyze the factors that influence it. This study uses customer relationship factors, administrative factors, technology factors, production processes, and supplier relationships as variables. The result achieved is knowing whether using SCM and e-business has an effect on the internal management of a company. Is a company that already uses SCM and e-business able to increase company productivity through automating information between partners in the supply chain, reducing operational costs for storing goods and integrating information between divisions within the company. This study uses the R Studio as a tool and performs calculations using the pearson correlation analysis method.